2021
DOI: 10.1145/3451342
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Intel Optane Memory for Managed Workloads

Abstract: Intel Optane memory offers non-volatility, byte addressability, and high capacity. It suits managed workloads that prefer large main memory heaps. We investigate Optane as the main memory for managed (Java) workloads, focusing on performance scalability. As the workload (core count) increases, we note Optane’s performance relative to DRAM. A few workloads incur a slight slowdown on Optane memory, which helps conserve limited DRAM capacity. Unfortunately, other workloads scale poorly beyond a few core counts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Second, although its write latency is relatively low, it is still orders of magnitude high compared to DRAM. Furthermore, its memory cell write endurance (10 8 -10 9) is orders of magnitude lower than that for DRAM although it is claimed that it is enough to survive continuous operation as the main memory for a few years [83]. Flash memory is an electronic NVM storage medium that can be electrically erased and reprogrammed.…”
Section: Nvm Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, although its write latency is relatively low, it is still orders of magnitude high compared to DRAM. Furthermore, its memory cell write endurance (10 8 -10 9) is orders of magnitude lower than that for DRAM although it is claimed that it is enough to survive continuous operation as the main memory for a few years [83]. Flash memory is an electronic NVM storage medium that can be electrically erased and reprogrammed.…”
Section: Nvm Technologiesmentioning
confidence: 99%
“…FeRAM, which has similar structure as DRAM bit cell except, achieve nonvolatility, it utilizes a ferroelectric layer instead of a dielectric layer. This technology has been gaining popularity, especially in industrial IoT applications and autonomous vehicles field, for its unique characteristics such as having very high life endurance, low write time speed, and low write energy consumption [83]. However, like any other technology in NVM category, it faces some limitations that hinders this technology from its widespread use, such as much lower storage densities than Flash, storage capacity limitations and higher cost.…”
Section: Nvm Technologiesmentioning
confidence: 99%
“…Some other projects employ application-level tools to tag and profile certain data structures, and then use heuristic models to assign objects to the appropriate tier [2,4,18,42,63,66]. While these efforts demonstrate that application guidance can be useful for certain usage scenarios, they require manual source code modifications or expensive online detection to attach recommendations to data objects.…”
Section: Software-directed Heterogeneous Memory Managementmentioning
confidence: 99%
“…All guided and non-guided configurations use SICM with the unmodified jemalloc allocator (v. 5.2.0) with oversize_threshold set to 0, background_thread set to true, and max_background_threads set to 1. 4 To prepare executables for guided execution, we configure the compilation pass to clone up to three layers of call path context to each allocation site. Our previous work has shown that this amount of context is sufficient to obtain the benefits of this approach for most applications [21,61].…”
Section: Common Experimental Configurationmentioning
confidence: 99%
See 1 more Smart Citation